Meninjau Ulang Sustainable Development: Kajian Filosofis Atas Dilema Pengelolaan Lingkungan Hidup di Era Post Modern - Muthmainnah, Lailiy; Mustansyir, Rizal; Tjahyadi, Sindung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This study is an attempt to re-question the base argumentsÂ forsustainable developmentproposal with regardto environmental management. This attempt is important considering intensive deploymemt of cost and benefit calculations in every environmental management policy, which rooted in the utilitarian philosophical tradition. This researchÂ runs in the area ofÂ political philosophyandemploys methodicalÂ components includingdescription, interpretation, critical analysis, and verstehen.Â The currentÂ research suggests that the emergence of sustainable developmentÂ as a concept of environment management goes along withÂ modernity with allÂ issuesÂ that itÂ brings.Â The proposal ofÂ sustainable developments can be categorized into constructive postmodernismapproach. TheÂ main purpose of this proposalÂ is to create a condition of balance between the needs of the present generation and the adequacy of the needs ofÂ theÂ future generations. However,Â the concept appearsÂ to raise a newÂ concern consideringÂ the meaning ofÂ â€œsustainabilityâ€has become contestation with strong tendencyÂ to economicconsideration which reducesÂ the calculation of cost-benefits into cash-value calculations. ThisÂ reductionis tendency leads to aÂ dilemmaÂ considering the aspiration ofÂ shiftinganthropocentrism to ecocentrismunderlying behind concept ofÂ sustainable development willÂ ironically produce aÂ new forms of anthropocentrism.